Rescuing compound bioactivity in a secondary cell-based screening by using γ-cyclodextrin as a molecular carrier - Claveria-Gimeno R (Dove Medical Press, 2015)
Rafael Claveria-Gimeno,1–3 Sonia Vega,3 Valeria Grazu,4 Jesús M de la Fuente,4–6 Angel Lanas,2,8–10 Adrian Velazquez-Campoy,2,3,7 Olga Abian1–3,8 1Instituto Aragonés de Ciencias de la Salud (IACS), Zaragoza, Spain; 2IIS Aragón, Zaragoza, Spain; 3Institute of Biocomputation and Physics of Complex Systems (BIFI), Joint Unit IQFR-CSIC-BIFI, Universidad de Zaragoza, Zaragoza, Spain; 4Instituto de Nanociencia de Aragon (INA), Universidad de Zaragoza, Zaragoza, Spain; 5Instituto de Ciencia de Materiales de Aragón (ICMA), CSIC-Universidad de Zaragoza, Zaragoza, Spain; 6Institute NanoBiomedicine and Engineering, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 7Fundacion ARAID, Government of Aragon, Spain; 8Centro de Investigación Biomédica en Red en el Área Temática de Enfermedades Hepáticas y Digestivas (CIBERehd), Barcelona, Spain; 9Servicio de Aparato Digestivo, Hospital Clínico Universitario Lozano Blesa, Zaragoza, Spain; 10Department of Medicine, University of Zaragoza, Zaragoza, Spain Abstract: In vitro primary screening for identifying bioactive compounds (inhibitors, activators or pharmacological chaperones) against a protein target results in the discovery of lead compounds that must be tested in cell-based efficacy secondary screenings. Very often lead compounds do not succeed because of an apparent low potency in cell assays, despite an excellent performance in primary screening. Primary and secondary screenings differ significantly according to the conditions and challenges the compounds must overcome in order to interact with their intended target. Cellular internalization and intracellular metabolism are some of the difficulties the compounds must confront and different strategies can be envisaged for minimizing that problem. Using a novel screening procedure we have identified 15 compounds inhibiting the hepatitis C NS3 protease in an allosteric fashion. After characterizing biophysically the interaction with the target, some of the compounds were not able to inhibit viral replication in cell assays. In order to overcome this obstacle and potentially improve cellular internalization three of these compounds were complexed with γ-cyclodextrin. Two of them showed a five- and 16-fold activity increase, compared to their activity when delivered as free compounds in solution (while γ-cyclodextrin did not show antiviral activity by itself). The most remarkable result came from a third compound that showed no antiviral activity in cell assays when delivered free in solution, but its γ-cyclodextrin complex exhibited a 50% effective concentration of 5 µM. Thus, the antiviral activity of these compounds can be significantly improved, even completely rescued, using γ-cyclodextrin as carrier molecule. Keywords: primary and secondary screenings, drug activity, antiviral compounds, cyclodextrins, vehiculization, drug delivery, hepatitis C, NS3 protease, virus replicon system